#### Answer

$-1$

#### Work Step by Step

Step 1: $i^{-10}$ = $\frac{1}{i^{10}}$ = $\frac{1}{(i^{2})^{5}}$
Step 2: Since $i^{2}=-1$, the expression becomes $\frac{1}{(-1)^{5}}$
Step 3: After simplifying, $\frac{1}{(-1)^{5}}$ = $-1$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$-1$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.